Family Conflict in Marriage Story Movie Script by Noah Baumbach - Desfi Sarianti Anton Rante; Dahlia D. Moelier; Asyrafunnisa Asyrafunnisa (Humaniora: Journal of Linguistics, Literature, and Education, 2022)
The aims of this study were to identify types of family conflict and identify factors also the impact of family conflict on the main character in the Marriage Storymovie script by Noah Baumbach. The author uses descriptive qualitative research with a sociological approach and the theory of types of family conflict by Ursula Lehr and the theory of factor of family conflict by Sadarjoen. The results of the research show that in Marriage Story movie script, there are six types of family conflicts, namely; conflicts with parents, conflicts with child, conflicts with other people, conflict among husband and wife, conflicts of job selection and inner conflicts. Then, there are four factors that influence family conflict namely; economy, child, communication failures and jealousy. This type of family conflict and its factors then have an impact on the breakdown of marriages, fights in the divorce process, struggles for child custody, and distribution of assets.